The Second Amendment : the right to bear arms - Larson, Kirsten W. (2018)
Examines what caused the Second Amendment to be born and what effects the amendment has had throughout history.
Guns in early America -- Why was the Second Amendment written? -- Writing the Second Amendment -- What effect did the Second Amendment have? -- The Second Amendment today.
Includes bibliographical references and index.
Grades 4+
Keywords: United States. -- Juvenile literature; Firearms -- Law and legislation -- United States -- Juvenile literature